2021
DOI: 10.15376/biores.16.3.5301-5312
|View full text |Cite
|
Sign up to set email alerts
|

Classification of softwoods using wood extract information and near infrared spectroscopy

Abstract: Three kinds of softwoods (Douglas fir, radiata pine, and Sugi) were used to test the possibility of their classification via near infrared (NIR) spectroscopy. In a previous study, the authors presented that the content of Korean softwood extractives (larix, red pine, Korean pine, cedar, and cypress) influenced wood classification. For expanding the extent of wood species to be considered in the analysis, three foreign wood species were newly introduced. Prior to comparing the NIR spectra obtained from the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A significant peak at about 1675 nm occurred in PC-3, which was associated with the first overtone of C ar -H stretching vibrations from the lignin aromatic groups [23]. Park and Yeon et al reported that the contents and types of extractives can affect the identification of softwood using NIR spectra [24][25][26]. The NIR spectral features contain extractive information, and the extractives played an important role in identifying the 25 timbers in the proposed method.…”
Section: Wood Identification Based On Shorter Nir Band Fused Glcm Featuresmentioning
confidence: 99%
“…A significant peak at about 1675 nm occurred in PC-3, which was associated with the first overtone of C ar -H stretching vibrations from the lignin aromatic groups [23]. Park and Yeon et al reported that the contents and types of extractives can affect the identification of softwood using NIR spectra [24][25][26]. The NIR spectral features contain extractive information, and the extractives played an important role in identifying the 25 timbers in the proposed method.…”
Section: Wood Identification Based On Shorter Nir Band Fused Glcm Featuresmentioning
confidence: 99%
“…Among these classification schemes, the spectral analysis scheme has the advantages of fast speed, high accuracy, and non-destructive testing. For example, Park et al (2021) classified three coniferous wood species by use of wood extract and its near-infrared spectrum. Ma et al (2021) proposed a new classification for 15 wood species based on spatially resolved diffuse reflection (i.e., wavelength range 600 to 1000 nm).…”
Section: Introductionmentioning
confidence: 99%